Development of Bot for Microservices Server Monitoring Using Life Cycle Approach to Network Design Method - Setyadhi Putra Deriyanto; Heru Agus Santoso (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2020)
This study was conducted on the emergency response system that has been implemented in Demak, Kendal and Batang districts, namely Tanggapin. This system provides services in the form of reporting and actions, as well as information about the health sector, from the availability of hospital rooms to the availability of blood at PMI. Tanggapin uses a mobile-based and web-based platform, where the web is used as a medium for operators to input data and validate incoming reports. Due to complex system services with various supporting features, it requires a microservices architecture to operate independently and in a distributed manner. Because of this dynamic system, realtime monitoring support for server performance is needed via Telegram Bot. The monitoring system was built using the PPDIOO Lifecycle Approach to Network Design and Implementation method because it is reliable and the flow of a process never breaks. The format used to exchange data uses the JSON (Javascript Object Notation) format. This study shows that the monitoring system run well because every test carried out gives the expected results, namely the admin receives a warning message via the Telegram Bot.